Fuzzy Γ-Hyperideals in Γ-Hypersemirings by Using Triangular Norms - Ersoy, B. A.; Davvaz, B.; Onar, S.; Leoreanu-Fotea, V. (HINDAWI LTD, 2014)
The concept of Gamma-semihyperrings was introduced by Dehkordi and Davvaz as a generalization of semirings, semihyperrings, and Gamma-semiring. In this paper, by using the notion of triangular norms, we define the concept of triangular fuzzy sub-Gamma-semihyperrings as well as triangular fuzzy Gamma-hyperideals of a Gamma-semihyperring, and we study a few results in this respect.
Keywords: Science & Technology - Other Topics